COSTANZA CARAFFA, ed., Photo Archives and the Photographic Memory of Art History - Rowat, Theresa (Archivaria, 2013)
Photo Archives and the Photographic Memory of Art History . COSTANZA CARAFFA, ed. Berlin, München: Deutscher Kunstverlag, 2011. 456 p. ISBN 978-3-422-07029-5.